2002
DOI: 10.3201/eid0805.010251
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants ofEhrlichia phagocytophila1,Rhode Island and Connecticut

Abstract: Primers were used to amplify a 561-bp region of the 16S rRNA gene of Ehrlichia phagocytophila from Ixodes scapularis ticks and small mammals collected in Rhode Island and Connecticut. DNA sequences for all 50 E. phagocytophila-positive samples collected from 1996 through 1998 in southwestern Connecticut were identical to the sequence reported for E. phagocytophila DNA from confirmed human cases. In contrast, the sequences from 92 of 123 E. phagocytophila-positive Rhode Island samples collected from 1996 throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 28 publications
1
106
1
Order By: Relevance
“…Phylogenetic analysis of this region of the gene failed to resolve any well-supported divergence among the 'strains' examined, including those of UK sheep isolates and isolates associated with disease in humans, even though variations in this region of the gene have been reported to have ecological significance (Massung et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis of this region of the gene failed to resolve any well-supported divergence among the 'strains' examined, including those of UK sheep isolates and isolates associated with disease in humans, even though variations in this region of the gene have been reported to have ecological significance (Massung et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already suggested that variations in either 16S rRNA gene or p44 sequences from USA isolates may be associated with ecological or clinical characteristics of A. phagocytophilum (Carter et al, 2001;Massung et al, 2002). In the present study, we have investigated the hypothesis that differences in either 16S rRNA gene or p44 sequences may occur amongst UK isolates from ruminants (that have yet to be associated with human disease), and isolates from other parts of the world, particularly the USA, where human disease does occur.…”
Section: Introductionmentioning
confidence: 99%
“…Roe deer (Capreolus capreolus) in Spain, Austria and the Czech Republic, wild boars (Sus scrofa) in the Czech Republic and foxes (Vulpes vulpes) in Austria have also been shown by molecular tools to be exposed to this bacteria [99,111]. Usually, genetic variants are often identified when A. phagocytophilum is detected in vectors, people or animals [86].…”
Section: Natural History Of Anaplasma Phagocytophilummentioning
confidence: 99%
“…Previously, Massung et al suggested that distribution of the genetic variants of A. phagocytophilum (formerly Ehrlichia phagocytophila) are likely to be associated with ecological factors that support their maintenance in the natural environment and that competition between a human agent and its variants may influence incidence of clinical cases (11). Our previous study showed that only two base pairs of 16S rDNA were different among the three genetic variants of Ehrlichia sp.…”
mentioning
confidence: 99%